POLA KOMUNIKASI KELUARGA HINDU DI ERA DIGITAL DALAM MEMBENTUK KARAKTER ANAK USIA DINI DI KELURAHAN BANYUNING KECAMATAN BULELENG KABUPATEN BULELENG - Ni Putu Ayu Desi Wulandari; I Gede Sutarya; I Gusti Made Widya Sena (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
The family is the spearhead in the formation of the child's personality because the family has the most important role in the issue of children's education, and the family is the place where children grow and develop from birth to adulthood. Therefore, education in the family must be a major concern. Parents who communicate well, can be considered friends by children and will make a warm life in the family, so that between parents and children have openness and give each other. Besides that, children are given the freedom to express various opinions, ideas, desires, feelings, and the freedom to respond to the opinions of others. Children who live with effective parental communication patterns will produce children's personalities who can control themselves, independent children, have good relationships with friends, and are able to face various problems in their lives. The method used in this research is qualitative with descriptive research type. Primary data sources were obtained by interviewing informants, secondary data sources were obtained from literature studies, literature and documentation.